Spectrophotometric Determination of Gemifloxacin Mesylate in Pharmaceutical Formulations Through Ion-Pair Complex Formation - Marothu Vamsi Krishna; Dannana Gowri Sankar (E-Journal of Chemistry)
Four simple and sensitive ion-pairing spectrophotometric methods have been described for the assay of gemifloxacin mesylate (GFX) either in pure form or in pharmaceutical formulations. The developed methods involve formation of colored chloroform extractable ion-pair complexes of the drug with safranin O (SFN O) and methylene blue (MB) in basic medium; Napthol blue 12BR (NB 12BR) and azocaramine G (AG) in acidic medium. The extracted complexes showed absorbance maxima at 525, 650, 620 and 540 nm for SFN O, MB, NB 12BR and AG, respectively.Beer's law is obeyed in the concentration ranges 3-15, 4-20, 2-10 and 2-10 μg/mL with molar absorptivity of 2.81 × 104, 2.20 x 104, 4.02 × 104 and 4.15 × 104 L mole−1 cm−1 and relative standard deviation of 0.077, 0.104, 0.080 and 0.103% for SFN O, MB, NB 12BR and AG, respectively. These methods have been successfully applied for the assay of drug in pharmaceutical formulations. No interference was observed from common pharmaceutical adjuvants. Results of analysis were validated statistically and through recovery studies.